(untitled) (Indian Journal of Child Health, 2020)
Introduction: Acute kidney injury (AKI) occurs frequently in preterm neonates and is associated with increased morbidity and mortality. Objective: The objective of the study was to study the association between caffeine administration and risk of early AKI occurring in the first 7 days after birth and the severity of AKI, defined by modified neonatal Kidney Disease Improving Global Outcomes (KDIGO) staging. Materials and Methods: The present study was a retrospective observational cohort of 100 preterm babies admitted in neonatal intensive care unit of a tertiary hospital of South India. All preterm babies with 2 or more serum creatinine (sCr) values were included in this study and neonates with death within 48 h after birth, <1 day of measured urine output on days 2–7 after birth, and fewer than 2 sCr measurements were excluded from the study. Caffeine exposure was determined by review of the inpatient medication record. Results: A total of 100 preterm cases were included, out of which 57 cases received caffeine and rest 43 did not. There were 29 cases (29%) who developed AKI in the first 7 days after birth and 9 cases developed Grade 1, 14 cases developed Grade 2, and 6 cases developed Grade 3 AKI according to modified KDIGO guidelines. Neonates who received caffeine were less likely to develop early AKI compared with those who did not (17.5% vs. 44.2%, p=0.004). Conclusion: Caffeine administration in preterm neonates is associated with reduced occurrence and severity of AKI. Because of the beneficial effects of caffeine, it may be reasonable to consider its routine use in preterm neonates to prevent or reduce AKI.